UPAYA MENINGKATKAN BRAND AWARENESS PRODUK SARIAYU MELALUI MACS STRATEGIC - Yuli Setiawan (Jurnal Manajemen, 2024)
The cosmetics industry in Indonesia experienced growth of up to 20.6%. In July 2022, the cosmetics industry increased from 819 to 913; SMEs dominated this increase at 83%. The market potential for body care products (skincare) in Indonesia is due, in part, to the increasing number of young people or the millennial generation. The total market in Indonesia has reached 267 million people, with a demographic population of women running 130 million people, and around 68% of them are women of productive age. Due to the enormous potential of skincare products in the Indonesian market, cosmetics entrepreneurs have emerged by bringing new brands and offering various advantages and modern marketing strategies. This condition is a big challenge, especially for old skincare entrepreneurs whose brands have long been known to the Indonesian public, one of which is Sariayu from Martha Tilaar. This research uses qualitative methods, which refer to journal data collection, expert opinions, and interviews, to obtain a formula for the Sariayu business development strategy. MACS's strategy can be a recommended solution for improving the branding of Sariayu's product.